Tradisi Ziarah dalam Masyarakat Jawa Perspektif Filsafat Nilai Max Scheler - Eni Latifah (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This research aimed to reveal the tradition of visiting graves in Javanese society from the perspective of Max Scheler's philosophy of value. This research was a type of field research using descriptive qualitative methods by collecting data obtained from observation, interviews, and documentation. As for data analysis, namely description, interpretation, induction and deduction, internal coherence, holistic, internal continuity, heuritics, and inclusive or analogical language. The research results showed that the pilgrimage tradition adheres to philosophical values, namely enjoyment, life, psychology, and religion. The stages of values obtained in the Pilgrimage tradition in Max Scheler's perspective were: First, the value of pleasure was reflected in the enthusiasm of the community such as togetherness, cohesiveness, enjoying free-range chicken ingkung after a joint prayer ritual. Second, mutual cooperation in order to clean the graves of grandparents or guardians. Third, the spiritual value when reading the consent and followed by a prayer followed by the community holding the event. Fourth, the value of holiness with the aim of getting blessings from the Creator (God).